Examine the quality of honey in the Tahura Lati Petangis area as an effort to increase market value - Rahayu, Ibnu Eka; Kurnyawaty, Noorma; Wijayanti, Anik; Bastomy, Imam (Community Empowerment, 2021)
Tahura Lati Petangis has officially become a forest area through the Decree of the Minister of Environment and Forestry Number SK.4335/MenLHK-PKTL/KUH/2015. In accordance with the Lati Petangis Tahura Management Plan Document 2019-2028, the Utilization Block will be designated for the development of ecotourism, educational tourism, environmental services and appropriate plant development. The development of ecotourism in the Tahura area is the cultivation of pollinating insects, namely honey bees with Trigona sp. which produces kelulut honey products. Kelulut honey products will be more valuable in the market if their quality and safety are guaranteed in accordance with the quality requirements listed in SNI. This community service aims to assist community groups in the Tahura area by testing the resulting kelulut honey products, so as to increase market value. The test results show that in general, all the honey tested has met the standard honey parameters which guarantee the purity of the honey produced in the Tahura Lati Petangis area where kelulut honey has a sourer taste than forest honey. The typical honey produced in the Tahura Lati Petangis area has a sweet-sour taste that is very good for consumption to maintain and increase body stamina.